7(9-3x)-2(x-3)=13

Simple and best practice solution for 7(9-3x)-2(x-3)=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(9-3x)-2(x-3)=13 equation:


Simplifying
7(9 + -3x) + -2(x + -3) = 13
(9 * 7 + -3x * 7) + -2(x + -3) = 13
(63 + -21x) + -2(x + -3) = 13

Reorder the terms:
63 + -21x + -2(-3 + x) = 13
63 + -21x + (-3 * -2 + x * -2) = 13
63 + -21x + (6 + -2x) = 13

Reorder the terms:
63 + 6 + -21x + -2x = 13

Combine like terms: 63 + 6 = 69
69 + -21x + -2x = 13

Combine like terms: -21x + -2x = -23x
69 + -23x = 13

Solving
69 + -23x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-69' to each side of the equation.
69 + -69 + -23x = 13 + -69

Combine like terms: 69 + -69 = 0
0 + -23x = 13 + -69
-23x = 13 + -69

Combine like terms: 13 + -69 = -56
-23x = -56

Divide each side by '-23'.
x = 2.434782609

Simplifying
x = 2.434782609

See similar equations:

| 42=x+3x+10 | | 4t=24+t | | 342x+345=755553 | | -7x+4+2x=4 | | 5x+5+x=-55 | | 2x^2+2y^2-xy-15x+30=0 | | 5+x+4x=40 | | 4x-2+4x=86 | | y=-.0375x^2+2.5x+.025 | | -5+6x=43 | | 8+6x=-58 | | -12s-48=12 | | 10m-10=-3 | | -9t-4=5 | | 6x+9=69 | | 35=-5(2s+10) | | -8n+2=34 | | -6.1(3t+5)-2.2(4t-6)= | | 6x+1=-35 | | 10y+50=170 | | 10y+50=179 | | 0.75=not+0.6 | | 36=3v-10 | | 12(t-4)+6t=6(3t+3)-12 | | n-7n-10=n+3n+30 | | 54=2u+16 | | (-4)*(-3)= | | 3*(-3)= | | 3*(-3)*(-4)*(-3)= | | b^2-7b=18 | | 2x+8x-(6x+7)= | | 4x+15-15+3-8x=13 |

Equations solver categories